Comparison of chromatographic profiles of essential oils in extracts of 13 species from Lamiaceae family - K. O. Khohklova; L. I. Vyshnevska; O. A. Zdoryk (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The TLC essential oils profiles were being used conventionally for identification of herbal raw materials (HRM) of Lamiaceae family. Despite this, in recent years the European Pharmacopoeia to call in question the appropriateness of TLC on essential oils determination of Thyme and Wild Thyme, as well as Peppermint and Peppermint dry extract; these methods were replaced by HPTLC using ﬂavonoid proﬁle. This work aimed to establish the possibility of conducting HPTLC identification of methanolic extracts of 13 members of the Lamiaceae family in harmonized chromatographic conditions using chromatographic profiles on essential oils. The objects were methanolic extracts of HRM of Ukraine flora - Salvia officinalis, Salvia aethiopis, Thymus serpyllum, Thymus vulgaris, Origanum vulgare, Rosmarinus officinalis, Ocimum tenuiflorum (foreign origin), Mentha × piperita, Melissa officinalis, Orthosiphon stamineus, Agastache foeniculum, Leonurus cardiaca, Hyssopus officinalis, Marrubium vulgare, prepared from HRM that were purchased in Ukraine. The study wоas done by standardized HPTLC procedure using automatic HPTLC herbal system of CAMAG, Switzerland, at the base of CAMAG laboratory, Muttenz, Switzerland, and laboratory of ESTCCTI ESIPP, NUPh, Ukraine. Chromatography conditions: stationary phase - HPTLC plates Si 60 F254; mobile phase - toluene-ethylacetate (95:5); reference standards - borneol, bornyl acetate, cineole; derivatization - anisaldehyde reagent; detection: WRT, 254, 366 nm - before derivatization; WRT, 366 nm - after derivatization; sample preparation - methanolic extracts (100 mg/ml), extracted by shaking technique. In unified chromatographic conditions the HPTLC chromatographic fingerprints of essential oils of 13 Lamiaceae family species were established and evaluated. The most specific, intensive and reproducible HPTLC fingerprints were for Sage and Rosemary extracts. Moreover, fingerprints of Sage, Thyme, Rosemary, Origanum, Ocimum and Peppermint shown specific zones useful for differentiation of different genera of Lamiaceae family. For setting relative acceptance criteria for each of the species the validation for specific zones that were detected should be done.